The relative caloric prices of healthy and unhealthy foods differ systematically across income levels and continents - Headey, Derek D.; Alderman, Harold (American Society for Nutrition, 2019)
Relative prices of healthy/unhealthy foods have been implicated in the obesity epidemic, but never extensively quantified across countries or empirically linked to undernutrition.